Analisis Sistem Manajemen Risiko pada Perusahaan Gadai untuk Mendorong Peningkatan Kualitas Pelayanan di Jakarta Tahun 2025 - Erlinda Argiyanti; Azmal Hali; Galuh Ratna Manggalih; Halimahtus Sadiah; Savira Damayanti; Ahmad Setiawan Nuraya (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The rapid development of Indonesia’s pawnshop industry has increased operational complexity and exposed companies to diverse risks that, if not well managed, may disrupt service quality and business continuity. Although pawnshop institutions are required to adopt structured risk management aligned with Enterprise Risk Management (ERM), many still rely on fragmented practices that depend heavily on managerial judgment. This study aims to analyze the adequacy of the risk management system implemented by a pawnshop company in Jakarta and identify the dominant risks affecting its daily operations. A qualitative descriptive approach was employed, using in-depth interviews with unit leadership, direct observations of service processes, and supporting secondary data such as financial reports and historical collateral trends. Risk identification and assessment were conducted through the ERM framework, using a likelihood impact matrix to classify operational, strategic, financial, and external risks. The results show that several high-risk exposures persist, including counterfeit gold items, appraisal inaccuracies related to digital system errors, cybersecurity threats, credit and auction challenges, and volatility in gold market prices. The findings also reveal that existing mitigation efforts remain partially integrated due to the absence of a dedicated risk management unit. Strengthening internal controls, improving appraisal and digital capabilities, and enhancing cybersecurity preparedness are essential to achieving more consistent service quality and reducing vulnerability to unexpected losses.